CAMTASIA STUDIO DASTURIDA PASKAL TILINING GRAFIK IMKONIYATLARI AKS ETTIRILGAN VIDEODARS YARATISH - S.P. Kutliyev; SH.B. Qushimmatova; G.R. Quvondiqova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article discusses Camtasia Studio and its features. The graphic possibilities of Pascal language are shown, the creation of a video tutorial is explained with practical methods.